Analisis Determinasi Konservatisme Akuntansi Perusahaan Pertambangan Terdaftar Bursa Efek Indonesia Tahun 2017 – 2021 - Eko Triyanto; Arif Nugroho Rachman; Firman Fauzi Ibrahim (Jurnal Akuntansi dan Pajak, 2023)
This research was aimed to examine the factors influence accounting conservatism by observing : (1) the influence of leverage on accounting conservatism (DAR), (2) the influence of financial distress on accounting conservatism (Almat Z-Score), (3) the influence of managerial ownership on accounting conservatism (Managerial Share), (4) the influence of institutional ownership on accounting conservatism (Institutional Share), (5) the influence of firm size on accounting conservatism (Ln Total Asset). Accounting conservatism as measured by Givoly and Hayn’s formula, is negative accrual measure . The population used in this study are mining companies listed on the Indonesia Stock Exchange period of 2017 – 2021. The Sample used in this study was collected using a purposive sampling method. The data used Is financial statement of 21 companies that resulting 105 object research. This study used multiple regression for data analysis. The results of this study are as follows : (1) the leverage has a positive significant influence to accounting conservatism, (2) the financial distres has negative significant influence to accounting conservatism, (3) the Managerial Ownership has a negative significant influence to accounting conservatism, (4) the institutional ownership has not influence to accounting conservatism, (5) the firm size has not influence to accounting conservatism. Keywords : Accounting conservatism, Firm size, Leverage, Managerial ownership, Financial distress, Institutional ownership